Shape Embedding: A Means of Superimposing Alternative Design Descriptions on Shape Models. (November 2022) - McKay, Alison; de Pennington, Alan
Abstract: In 1989, Shapiro and Voelcker introduced three principles for relating shape and function with the goal of establishing an appropriate formal role for geometry in a theory of mechanical design. This technical note contributes to the establishment of such a theory by using an example from their technical note to illustrate the potential value of incorporating shape embedding, used in the shape computation and shape grammar community to support shape synthesis, into CAD packages that are used primarily to support shape definition and analysis. Graphical abstract: Highlights: Recollections of collaborations with Prof Herb Voelcker since the early 1970s. There is a need, in engineering design, for multiple descriptions of a given design. These descriptions are used for different purposes through the lifecycle of a product. Embedding is a mechanism that can be used to superimpose multiple design descriptions on a given shape model. The use of embedding promises underlying consistency across design descriptions without the need for deep integration of said descriptions.